Spontaneous PMN apoptosis in type 2 diabetes and the impact of periodontitis. Issue 6 (11th October 2017) - Manosudprasit, Aggasit; Kantarci, Alpdogan; Hasturk, Hatice; Stephens, Danielle; Van Dyke, Thomas E.
Abstract : Peripheral blood neutrophils exhibit delayed spontaneous apoptosis in subjects with type 2 diabetes through an AGE/RAGE ligand/receptor‐mediated interaction. Abstract : The purpose of this study was to test the hypothesis that peripheral blood neutrophils (PMN) exhibit delayed spontaneous apoptosis in individuals with diabetes mellitus type 2 (T2DM) and that the delay is exacerbated further among people who coexpress chronic periodontitis (CP). Seventy‐three individuals were enrolled, including those with T2DM ( n = 16), CP ( n = 15), T2DM + CP ( n = 21), and healthy volunteers ( n = 21). PMN apoptosis was determined by flow cytometry using TUNEL and Annexin V assays. The activity of caspase‐3, ‐8, and ‐9 was measured by colorimetric assay. PMN surface death receptor quantification was performed by flow cytometry staining with fluorescence‐conjugated anti‐CD120a (TNFR1) and anti‐CD95 [Fas receptor (FasR)] antibody. Analysis of inflammatory markers in serum samples was performed using multiplexed sandwich immunoassays. In healthy volunteers and individuals with T2DM, CP, and T2DM + CP, spontaneous PMN apoptosis observed at 12 h reached 85.3 ± 3.1, 67.3 ± 3.9, 62.9 ± 3.5 and 62.5 ± 5.4%, respectively ( P < 0.05). Caspase‐3 activity was significantly reduced in individuals with T2DM and T2DM + CP ( P < 0.05) when compared with healthy volunteers. Caspase‐8 activity was also significantly decreased in CP and T2DM + CP ( P < 0.05), associated with reduced cell‐surface FasR, TNFRs, and Fas ligand (FasL) serum levels. Glucose alone was not observed to impact PMN apoptosis; simultaneous incubation with the receptor for advanced glycation endproducts (RAGE) agonist S100B induced significant PMN apoptosis ( P < 0.05). These data support the premise that the inhibition of PMN apoptosis in individuals with T2DM occurs through an advanced glycation endproducts/RAGE ligand/receptor‐mediated interaction.